Analisis Pengaruh Perubahan Penggunaan Lahan Terhadap Debit Banjir Di Sub DAS Kampar Kiri - Firdaus, Firdaus; Sujatmoko, Bambang; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Land use change in the watershed is a factor contributing to the flooding because it affects the ability of the soil to absorb water infiltration. This phenomenon is studied in Kampar Kiri sub- watershed that is located in watershed outlet of Lipat Kain water level recorder. This study aims to analyze the effect of land use change on the flood discharge in Kampar Kiri sub watershed. The calculation of flood discharge uses HEC-HMS. Input data modelsare daily rainfall data, land use maps of 2005 and 2011 and soil type maps. The results showed that there were significant changes in land use on open land and dry land farming mixed bush at -87,648% and -70,035%. Land conversion also occurs in dry forest primary, secondary dry forest, scrub, plantations, secondary swamp forest, mixed gardens, vegetation regularly, as well as plantations. While dryland farming settlements and an increase of 153,894% and 94,114%. This condition increases the value of Curve Number (CN) composite average in 2005 and 2011 amounted to 80,462 and 83,722 and the value imperviouss composite average of 2.884% and 3.507%. Peak flood discharge for 25 and 50 year return periode in 2005 that were obtained from the HEC-HMS modeling are 924,4 m3/sand 1096,4 m3/s respectively, and in 2011 are 932,8 m3/s and 1105 m3/s . Increasing of flood discharge because of lande use change for 25 year return periode are 8,4 m3/s (0,909%) andfor 50 year return periode are 8,6 m3/s (0,784%). Correction difference discharge (DE) between HEC-HMS modeling measurement data with 25 and 50 year return periode in 2005 are 1,153% and 5,468%, whereas in 2011 are 2,072% and 6,296% respectively.Keywords: land use, peak discharge, HEC-HMS, correction difference discharge